Effect of pore texture on performance of activated carbon supercapacitor electrodes derived from olive pits. (1st April 2015) - Redondo, Edurne; Carretero-González, Javier; Goikolea, Eider; Ségalini, Julie; Mysyk, Roman
Highlights: Olive pits were employed as the precursor for supercapacitor electrodes. Microporosity was tailored to provide optimum capacitive rate performance. A link between capacitance rate capability and textural properties was established. Abstract: Activated carbon electrodes for electrochemical capacitors have been prepared by the chemical activation of a natural renewable and by-product material precursor – olive pits – from the olive oil production industry. The careful adjustment of the synthesis conditions has allowed synthesizing a series of microporous carbon electrodes with an optimized microporosity, enabling a gravimetric and volumetric capacitance in basic aqueous medium up to 260 F g −1 and 140 F cm −3, respectively, with good rate capability. A relation amongst capacitance, specific surface area, accessible average pore size and effective dielectric permittivity has been established, demonstrating that there is not just a single parameter decisively impacting the capacitance value. The collective analysis of experimental data suggests that solvation imposes an optimum pore size for each ion with regard to rate capability: moderate solvation contributes to enhancing capacitance in pores slightly exceeding solvated ion size while excessive solvation deteriorates the high-rate response of supercapacitor electrodes having pores much wider than ion size.